Implementation of Simple Additive Weighting (SAW) Method To Determine Exemplary PKH Social Worker (Case Study: PPKH Garut Regency) (Buana Information Technology and Computer Sciences (BIT and CS), 2021)
One measure of the success of an employee in carrying out his job is his election as an exemplary employee in the agency where he works. The selection must of course be based on standard measurement and objective assessment, the goal is that the predetermined results can be justified. A decision support system using the Simple Additive Weighting (SAW) method can help PPKH Garut regency in determining exemplary PKH socialworker in each sub-district PPKH unit, this method will look for weight values for each predetermined criterion consisting of quantity, integrity, dedication, reliability, initiative, diligence, attitude, motivation and presence. The data sample taken in this research was PPKH X Sub-distric, where the results of the research are in the form of a ranking that can support the decision to choose an exemplary PKH social worker in PPKH Garut Regency